The Role of Islamic Education in Preventing Radicalism among Youth - Rajaminsah Rajaminsah; Amirudin Amirudin; Ajat Rukajat; Cece Hidayat; Sumarna Sueb; Saepudin Saepudin (Lafadz Jaya Publisher, 2024)
This study aims to examine the role of Islamic education in preventing radicalism among youth. The rise of radicalism, especially among the younger generation, is a major challenge to social stability and security in Indonesia. Inclusive and moderate Islamic education has great potential in building a peaceful and tolerant understanding of religion, as well as preventing the spread of extremist ideologies. This study uses a qualitative approach with the library research method. Data was obtained through observation, and analysis of documents. The results of the study show that the Islamic education curriculum that emphasizes the values of moderation, tolerance, and respect for differences can be a fortress for youth in facing radical narratives. In addition, the role of teachers and a conducive educational environment are also important in shaping anti-radicalism attitudes. This study recommends strengthening character education programs based on moderate Islamic values as a preventive effort in preventing radicalism among youth.